2017
DOI: 10.3390/sym9080128
|View full text |Cite
|
Sign up to set email alerts
|

Opposition and Identicalness: Two Basic Components of Adults’ Perception and Mental Representation of Symmetry

Abstract: Symmetry is a salient aspect of biological and man-made objects, and has a central role in perceptual organization. Two studies investigate the role of opposition and identicalness in shaping adults' naïve idea of "symmetry". In study 1, both verbal descriptions of symmetry (either provided by the participants or selected from among alternatives presented by the experimenter) and configurations drawn as exemplars of symmetry were studied. In study 2, a pair comparison task was used. Both studies focus on confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 81 publications
2
3
0
Order By: Relevance
“…Moreover, our two studies are not backed up by a great deal of previous research. However, having said that, there do seem to be three recurring outcomes relating to this paper which are in agreement with some earlier studies on opposition ( Bianchi and Savardi 2008b ; Bianchi et al 2014 , 2015 , 2017b , 2017c ). We will first briefly present these and then discuss the limitations of these conclusions which are due to the limitations relating to the studies.…”
Section: Final Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, our two studies are not backed up by a great deal of previous research. However, having said that, there do seem to be three recurring outcomes relating to this paper which are in agreement with some earlier studies on opposition ( Bianchi and Savardi 2008b ; Bianchi et al 2014 , 2015 , 2017b , 2017c ). We will first briefly present these and then discuss the limitations of these conclusions which are due to the limitations relating to the studies.…”
Section: Final Discussionsupporting
confidence: 92%
“…Furthermore, it appears that adults generally associate opposition with the idea of symmetry. The naïve representation of a symmetrical configuration does not only contain sameness, but also the presence of a visible opposition between the parts forming the symmetrical pattern ( Bianchi et al 2017b ). This is also an interesting aspect if we take into consideration the fact that in same–different tasks, pairs of symmetrical objects are sometimes used as exemplars of “the same”, as are stimuli showing two identical objects.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore (as discussed in Sections 1.2 and 3), the theoretical premise that the facilitation in this study is based on, in part connects to, but in part differs from, the theoretical ideas presupposed by the works cited above. In this sense, we trust that this study reveals the connections between the research into opposites (Bianchi et al 2011a(Bianchi et al , 2011b(Bianchi et al , 2013(Bianchi et al , 2017a(Bianchi et al , 2017b(Bianchi et al , 2017c and that into contrast sets and the iterative counterfactual strategy (Oaksford and Stenning 1992;Oaksford andChater 1994a, 1994b;Oaksford 2002).…”
Section: Introductionsupporting
confidence: 61%
“…This has emerged from language studies (e.g., Jones 2002Jones , 2007Paradis et al 2009) and perceptual studies that have shown that the perception of opposites is essential to spatial perception (e.g., Bianchi et al 2011aBianchi et al , 2013Bianchi et al , 2017aBianchi and Savardi 2018). There is also evidence that humans possess an intuitive idea of two opposite visual or acoustic configurations (Bianchi et al 2017b(Bianchi et al , 2017c, as well as of two opposite postures or gestures (e.g., Savardi 2008a, 2008b;Bianchi et al 2014). The primary intuition of opposition has its roots in infants ' pre-verbal categorization (e.g., Casasola 2008;Casasola et al 2003).…”
Section: Rationale For Testing the Effects Of Training Reasoners To "...mentioning
confidence: 99%
“…This approach (the main theoretical and methodological framework of which are summarized in Bianchi and Savardi, 2008a) has led to various experimental explorations of the abilities of adults and children to recognize whether certain configurations are "opposite" as compared to "different" or "similar" and to also produce opposite configurations. These explorations referred to various perceptual domains and contents and involved, for example, simple visual configurations (e.g., Bianchi and Savardi, 2006;Schepis et al, 2009;Savardi et al, 2010;Bianchi et al, 2017a), everyday objects and/or environments (e.g., Bianchi et al, 2011Bianchi et al, , 2013Bianchi et al, , 2017c, human body postures (e.g., Bianchi and Savardi, 2008b;Bianchi et al, 2014), and acoustic stimuli (e.g., Biassoni, 2009;Bianchi et al, 2017b). The results emerging from these studies indicated that (a) the participants were consistent in defining the point along a dimension at which a property stops being perceived as pertaining to one extreme of the dimension (e.g., near on the dimension near/far) and starts to be perceived as an instance of the opposite property (e.g., in this case far) or of an intermediate region with variations that are not perceived as pertaining to either one pole or the other (e.g., neither near nor far); (b) two configurations are perceived to be opposites when they show a maximum contrast in terms of a perceptually salient property-usually regarding the orientation or direction of the configuration-within a condition of otherwise overall invariance (some examples are provided in Figure 2); and (c) due evidently to this close connection between the perception of opposition and the perception of opposite orientation in an overall invariant configuration, opposition is also perceived in configurations involving mirror symmetry, including people's perception of their own body reflection in a plane mirror.…”
Section: Introductionmentioning
confidence: 99%